MENINGKATKAN HASIL BELAJAR ATLETIK NOMOR LARI 100 METER MELALUI LATIHAN PENGGUNAAN WRIST WEIGHTS SISWA KELAS X SMA NEGERI 1 MERANGIN - Ellya Roza, S.Pd., M.Pd (Fokus | Jurnal Pendidikan STKIP YPM Bangko, 2022)
This study aims to determine the improvement of athletic learning outcomes in the 100 meter sprint number through the use of the Wrist Weights tool in class X IPA 3 SMA Negeri 1 Merangin. The research method used is classroom action research with the subjects of class X IPA 3 SMA Negeri 1 Merangin consisting of 31 students. The research was conducted in two cycles of action. In the first and second cycles, an initial test of student performance was given, the teacher observed students' activities in practicing using Wrist Weights during practice in teaching and learning activities. The actions given by students are the result of reflection on the use of wrist weights in exercises in learning. The results of the evaluation and reflection of the entire first and second cycles. In the second cycle, the students' learning mastery results were 83.87% and the class average was 84.25%, while the success rate of the first cycle was only 70.97% and the class average was 79.77%. The increase from the first cycle to the second cycle is 4.48 points. Based on the results of the evaluation and reflection of the second cycle, the Physical Education teacher at SMA Negeri 1 Merangin was recommended to use Wrist Weights in the athletic learning of the 100 meter sprint number for students. Because learning using wrist weights helps teachers improve learning outcomes and make learning more interesting and varied